PROSPECTSOFUNMANNEDAERIALVEHICLE (DRONE) IN AGRICULTURE - Юн, Г. Н.; Мазур, М. С. (Science-based technologies, 2016)
By 2050, world population will exceed 9 billion people. According to some projections to feed the world’s population, the agricultural sector must increase production by 70%. The number of resources suitable for use in agriculture - land, water, energy - will decline. Here the farmers have to rely primarily on support of new technologies that not only increase production with limited resources, but also improve its effectiveness. Increased yields in crop production - a strategic task for Ukraine. The object of research is the comparative analysis of the market of production and export of wheat in leading countries of the world is carried out.As well as advanced direction of crop capacity increasing in agriculture with help of Unmanned Aviation System is considered. Practice shows that rural aircraft exceeds the performance processing ground equipment several times. It allows you to quickly carry out crops and their processing by pesticides, toxic chemicals, to make fertilizer, to monitor. The use of modern unmanned aerial vehicles will extend the benefits of small aircraft.